2010
DOI: 10.1038/leu.2010.33
|View full text |Cite
|
Sign up to set email alerts
|

Wilms’ tumor gene 1 protein represses the expression of the tumor suppressor interferon regulatory factor 8 in human hematopoietic progenitors and in leukemic cells

Abstract: Wilms' tumor gene 1 (WT1) is a transcription factor involved in developmental processes. In adult hematopoiesis, only a small portion of early progenitor cells express WT1, whereas most leukemias show persistently high levels, suggesting an oncogenic role. We have previously characterized oncogenic BCR/ ABL1 tyrosine kinase signaling pathways for increased WT1 expression. In this study, we show that overexpression of BCR/ ABL1 in CD34 þ progenitor cells leads to reduced expression of interferon regulatory fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 40 publications
(61 reference statements)
1
29
0
Order By: Relevance
“…This suppression is not a general consequence of BCR-ABL activity, as down-regulation of CRKL has no effect on IRF-8 expression. Vidovic et al (41) reported that the WT1 (Wilms tumor gene 1) tumor suppressor inhibits IRF-8 transcription in a BCR-ABL-dependent manner. An interaction between WT1 and STAT3 has been reported; it is possible that WT1 and STAT5 could similarly act to regulate IRF-8 expression (42).…”
Section: Discussionmentioning
confidence: 99%
“…This suppression is not a general consequence of BCR-ABL activity, as down-regulation of CRKL has no effect on IRF-8 expression. Vidovic et al (41) reported that the WT1 (Wilms tumor gene 1) tumor suppressor inhibits IRF-8 transcription in a BCR-ABL-dependent manner. An interaction between WT1 and STAT3 has been reported; it is possible that WT1 and STAT5 could similarly act to regulate IRF-8 expression (42).…”
Section: Discussionmentioning
confidence: 99%
“…Both isoforms are known from previous reports to be capable of both activation and repression. 43,[46][47][48][49][50] Our finding could indicate that, even though the dominant influence of both isoforms on the target genes seems to be activating, in our cellular context WT1 +KTS co-localizes more often than WT1 -KTS with repressive complexes. Importantly, it should be pointed out that our investigation was restricted to WT1 +17AA isoforms.…”
mentioning
confidence: 93%
“…Several factors that repress Irf8 have been also reported, including STAT5 [54], C/EBPβ [47], GATA1 [55], WT1 [56], and BCR-ABL (see below). Interestingly, a recent study reported that myeloid-derived suppressor cells (MDSCs) develop by attenuating IRF8 expression via STAT3 and STAT5 [57].…”
Section: Regulation Of Irf8 Expressionmentioning
confidence: 99%